Barozzi-Veiga. La filarmonica di Stettino - Basili, Giulio (Firenze Architettura, 2021)
The great form of civil architecture, a spotless white ‘Gothic cathedral’ which accommodates the function of a concert hall, is filtered by the external fragmentation, declaring the will to lead the scale back to a sort of domesticity, in order to conform to the consolidated urban context. This is a first insight, an instinctive response to the place, a suspended atmosphere that is made of elementary geometric shapes marked by light.